THE UTILIZATION OF TECHNOLOGY IN HISTORY LEARNING AT HIGH SCHOOLS IN KARANGANYAR REGENCY UNDER THE MERDEKA CURRICULUM - Dadan Adi Kurniawan (SOSIOEDUKASI, 2026)
The Merdeka Curriculum is designed to ensure the quality of education and to develop superior and competitive human resources capable of facing the global challenges of the 21st century based on modern technology. Teachers and students are required to utilize technology to explore student-centered knowledge and experiences. The purpose of this study was to determine teachers’ understanding of the Merdeka Curriculum, the importance of technology in history learning, and the extent to which teachers and students at Karanganyar High School have utilized technology in history learning. This study employs a descriptive-analytical qualitative approach, utilizing data sources such as informants, documents, and literature. The results of the study indicate that there are varying interpretations of the Merdeka Curriculum among history teachers at high schools in Karanganyar Regency; the role of technology in history learning in the modern era is highly significant, particularly in fostering active, creative, innovative, and engaging learning; and history teachers at Karanganyar High School have incorporated various new technologies into daily instruction, encompassing planning, implementation, and evaluation of learning.